Vehicle sizes & weights manual (J.J. Keller & Associates, 2011)
The Vehicle Sizes & Weights manual provide federal and state size & weight limitations plus requirements for overdimensional movements in easy-to-use format . Sections are divided state by state and contain requirements, procedures, and fees related to obtaining overdimensional and overweight permits. The information includes legal limitations for vehicle length, width, height and weight. The manual also covers insurance requirements, weekend and holiday restrictions, ports of entry, and regulatory agencies.
Keywords: Motor vehicles -- Standards -- Law and legislation -- United States.; elektronické knihy; electronic books